Effects of single and combined gestational phthalate exposure on blood pressure, blood glucose and gestational weight gain: A longitudinal analysis. (October 2021) - Gao, Hui; Zhu, Bei-bei; Huang, Kun; Zhu, Yuan-duo; Yan, Shuang-qin; Wu, Xiao-yan; Han, Yan; Sheng, Jie; Cao, Hui; Zhu, Peng; Tao, Fang-biao
Highlights: Phthalate diesters (PE) were measured in multiple urine samples during pregnancy. Hazard index (HI) for multiple phthalates was calculated for each urine sample. Components of metabolic syndrome were assessed as outcomes. Inconsistent outcome associations were observed for single PEs and metabolites. HI was associated with increased risks of GDM, HDOP and excessive GWG. Abstract: Few studies have investigated the association of gestational exposure to phthalate with metabolic risk and have reached inconsistent conclusions. Based on the Ma'anshan Birth Cohort, 3273 women were included in the present study. All participants provided up to three urine samples for 7 phthalate metabolite measurements. The hazard index (HI) was used to evaluate the cumulative risk of multiple phthalate coexposures. The outcomes of interest included hypertensive disorders of pregnancy (HDOP), gestational diabetes mellitus (GDM), and gestational weight gain (GWG). The incidences of HDOP, GDM, and excessive GWG were 5.93%, 13.09%, and 28.95%, respectively. Exposure to a single phthalate metabolite or a specific diester during the first trimester of pregnancy elevated blood pressure (BP) and fasting plasma glucose (FPG) in the third trimester and body weight gain throughout pregnancy. However, inverse relationships were revealed for some phthalate metabolites, which were inconsistent with the results of their diesters. The HI value during the first trimester was positively associated with subsequent BP, FPG, and GWG. In addition, HI during the first trimester increased the risks of GDM [odds ratio (OR) = 1.34, 95% confidence intervals (CIs) = 1.02–1.75)] and excessive GWG (OR = 1.76, 95% CIs = 1.41–2.19) in a linear manner thereafter. Notably, phthalates might directly increase maternal blood glucose and pressure, and these changes were secondary effects of the obesiogenic effects of certain phthalates. In conclusion, exposure to single and multiple phthalates during the first trimester of pregnancy increased the risks of maternal metabolic syndrome components. However, the conflicting findings between phthalates and their metabolites need to be interpreted carefully.